The Financial Feasibility Analysis of Freshwater Fishing Business in Tempe Lake Waters After Revitalization - Sudirman, Azisah Azzahra; Gobel, Muhammad Rizq; Putalan, Reinal; Pradilia, Andi Desiah (Program Vokasi UNG, 2024)
The freshwater fishing business in Lake Tempe is the main livelihood for the coastal societies around Lake Tempe. In recent years, there have been floods due to the overflow of Lake Tempe, which caused losses to fishermen. One of the causes is the high sedimentation every year. The lake revitalization program is the way to solve this problem. The revitalization process provides social and economic changes to the society in the Lake Tempe area It has an impact on improving the economy of fishermen's households. This research aimed to analyze the financial feasibility of freshwater fishing based on the fishing gear used, namely gill nets, longlines, and traps. This research was carried out on the coast of Lake Tempe, namely Tempe, Sabbangparu, Tanasitolo, and Belawa Districts in Wajo Regency from March to June 2022. The researchers chose the location in a purposive way. This research is survey research. Data analysis used financial analysis by looking at the net present value (NPV), Net Benefit Cost (net B/C), Internal Rate of Return (IRR), and Payback Period (PP). The results showed that the large profits obtained from the catching freshwater fish business in Lake Tempe using gill nets were 13,526,859 (IRD) per year, then the longline fishing gear gains a profit of 10,557,023 (IRD), and for fishing traps gear, the profit is7,548,808 (IRD). The acquisition of each financial analysis obtained by NPV>0, net B/C>1, IRR>the applicable interest rate is 5%, and the payback period is less than 5 years. Therefore, it concluded that these three types of fishing gear are feasible to be developed.